The boy who couldn't die - Sleator, William (Amulet, 2004)
When his best friend dies in a plane crash, sixteen-year-old Ken has a ritual performed that will make him invulnerable, but soon learns that he had good reason to be suspicious of the woman he paid to lock his soul away.